A reading kit for grade eight - Itani, Ghada Ahmad (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2006)
This project provides a reading kit reflecting the curricular objectives of cycle III set by the National Center for Educational Research and Development (NCERD). It emphasizes the following curricular traditional (listening, speaking, reading, and writing) and new (study skills, thinking skills, and cultural awareness) objectives as stated in the Intermediate Level Curricular Objectives. This project is meant to arm the novice and experienced teachers of grade eight in cycle three with one reading lesson. It consists of one reading passage integrating language skills that are based on and match one of the themes mentioned in the curriculum book, Sources of Energy, and some of the instructional objectives of the Lebanese curriculum set by the Lebanese educators. All the exercises are based on the reading selection which tackles that specific theme of cycle III in the Lebanese English language curriculum. This reading kit is to emphasize all the traditional and the new skill s, for they all make up a meaningful curriculum outcome. This lesson applies the new curriculum with its receptive (listening and reading) and productive (reading and writing) skills.
: Mémoire
Keywords: Cycle moyen L enseignement de la Langue Anglaise; Intermediate Education English Language Education